2010 22nd International Teletraffic Congress (lTC 22) 2010
DOI: 10.1109/itc.2010.5608741
|View full text |Cite
|
Sign up to set email alerts
|

Fastrack for taming burstiness and saving power in multi-tiered systems

Abstract: Burstiness (i.e., sudden surges)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In this paper, we consider to exploit this algorithm for identifying changes in cloud user demands. However, we also find that the algorithm in [10] cannot accurately detect the start and the end of some bursts. Especially, the end of a burst is easily missed because of the deficiency of the algorithm, which results in the unnecessary delay in the detection of changes from peak to idle.…”
Section: B Online Versionmentioning
confidence: 84%
See 3 more Smart Citations
“…In this paper, we consider to exploit this algorithm for identifying changes in cloud user demands. However, we also find that the algorithm in [10] cannot accurately detect the start and the end of some bursts. Especially, the end of a burst is easily missed because of the deficiency of the algorithm, which results in the unnecessary delay in the detection of changes from peak to idle.…”
Section: B Online Versionmentioning
confidence: 84%
“…In [10], an algorithm has been proposed to use I coupled with information about the current and previous arrival rates to detect changes in arrival intensities. In this paper, we consider to exploit this algorithm for identifying changes in cloud user demands.…”
Section: B Online Versionmentioning
confidence: 99%
See 2 more Smart Citations
“…Workloads with bursty session arrivals will have very large values for I a in the order of hundreds or thousands to indicate a clear deviation from the Poisson process. Caniff et al presented evidence of burstiness in real-life workloads [17]. In particular, the authors showed that the classic FIFA World Cup trace of web request arrivals has an index of dispersion value of 8400.…”
Section: Workload Scenario Parametersmentioning
confidence: 99%